Advanced Audio Compression For Lossless Audio Coding Using Ieee 1857.2 (International Journal of Engineering and Computer Science, 2018)
Developed by IEEE-SA (Standard Association) and released in August 2013, IEEE 1857.2 is the latest standard for lossless audio compression. This recent standard for advanced audio coding (AAC) is an efficient lossless audio codec (coding decoding) technique, in improving audio quality for compression and decompression, optimizing bandwidth during transmission, saving storage space, it also speeds up the video and audio streaming, and others video and audio data. It defines a set of tools to support specific audio coding functions, including general audio coding and lossless coding. This project presents the algorithms for lossless audio coding communication, the higher efficiency of this standard and other assets such as compression ratio, encoding and decoding speed of this standard. Different types of audio files have compressed and the results show a good compression ratio (CR) which depends on audio file type, and good encoding and decoding speed.